On the issue of distortion source identification on the example of a simplified model of electric power system - Anatoly Voloshko; Daniel Filyanin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the research is caused the changed structure of energy consumption associated with an increase in the proportion of non-linear loads and the need to reliable determination of distortion sources in the distribution network for the effective functioning of the system of penalties and sanctions. The main aim of the study: is to determine the sources of stress curve distortion in the point of common coupling on the example of a simplified model of electric power system. The methods used in the study. The operating modes of the model are calculated using the Simulink application, included in the software package Matlab 2014a. To build the model the authors used a simulation library SimPowerSystem, which includes mathematical models of individual elements of power equipment. When selecting the model parameters of the distribution network the active resistances that simulate cable line and load, were used to simplify the calculations. To determine the magnitude and sign of harmonic power flux the Fourier transform was applied. The results. The authors carried out the review of the existing methods for identification of distortion sources in the point of common coupling of the distribution network; their advantages and disadvantages were defined. On the example of a simplified model of electric power system the authors measured the sign and magnitude of the power of distortion sources in the point of common coupling and at the terminals of consumers with non-distortion and distortion loads. According to the results of the measurements the differences in the values of secondary harmonic power in the point of common coupling and at the terminals of consumers were defined. The authors identified some features of the distortion sources presence in the load and proposed a new approach to identify the sources of harmonics by using a harmonic power flux sense method, according to which it is recommended to move the point of measuring of the secondary harmonic power from the point of common coupling to terminals of consumers.